Recognition of Lipopolysaccharide and Activation of NF-κB by Cytosolic Sensor NOD1 in Teleost Fish - Bi, Dekun; Wang, Yue; Gao, Yunhang; Li, Xincang; Chu, Qing; Cui, Junxia; Xu, Tianjun (Frontiers in Immunology, 2018)
Lipopolysaccharide (LPS) is the major component of the outer membrane of Gram-negative bacteria. This molecule can induce strong immune response and various biological effects. In mammals, TLR4 can recognize LPS and induce inflammatory response. However, the innate receptor in fish for recognizing LPS remains ambiguous. LPS can invade the cytoplasm via outer membrane vesicles produced by Gram-negative bacteria and could be detected by intracellular receptor caspase-11 in mammals, so, there may also exist the intracellular receptors that can recognize LPS in fish. NOD1 is a member of NOD-like receptors family and can recognize the iE-DAP in the cytoplasm in mammals. In fish, NOD1 can also respond to infection of Gram-negative bacteria and may play an important role in the identification of bacterial components. In this study, to study whether NOD1 is a recognition receptor for LPS, we detected the expression of NOD1 and several cytokines at transcript levels to determine whether LPS can induce inflammatory response in teleost fish and NOD1 can respond to LPS. Then, we perform the binding analysis between NOD1 and ultrapure LPS by using Streptavidin pulldown assay and enzyme-linked immunosorbent assay to prove that NOD1 can be combined with LPS, and using dual luciferase reporter gene assay to verify the signal pathways activated by NOD1. Next, through cell viability analysis, we proved that LPS-induced cytotoxicity can be mediated by NOD1 in fish. The results showed that NOD1 can identify LPS and activate the NF-κB signal pathway by recruiting RIPK2 and then promoting the expression of inflammatory cytokines to induce the resistance of organism against bacterial infection.